Platelet Transfusions in Pediatric Intensive Care*. Issue 9 (September 2016) - Du Pont-Thibodeau, Geneviève; Tucci, Marisa; Robitaille, Nancy; Ducruet, Thierry; Lacroix, Jacques
Abstract : Objectives: To characterize the determinants of platelet transfusion in a PICU and determine whether there exists an association between platelet transfusion and adverse outcomes. Design: Prospective observational single center study, combined with a self-administered survey. Setting: PICU of Sainte-Justine Hospital, a university-affiliated tertiary care institution. Patients: All children admitted to the PICU from April 2009 to April 2010. Intervention: None. Measurements and Main Results: Among 842 consecutive PICU admissions, 60 patients (7.1%) received at least one platelet transfusion while in PICU. In the univariate analysis, significant determinants for platelet transfusion were admission Pediatric Risk of Mortality Score greater than 10 (odds ratio, 6.80; 95% CI, 2.5–18.3; p < 0.01) and Pediatric Logistic Organ Dysfunction scores greater than 20 (odds ratio, 26.9; 95% CI, 8.88–81.5; p < 0.01), history of malignancy (odds ratio, 5.08; 95% CI, 2.43–10.68; p < 0.01), thrombocytopenia (platelet count, < 50 × 10 9 /L or < 50, 000/mm 3 ) (odds ratio, 141; 95% CI, 50.4–394.5; p < 0.01), use of heparin (odds ratio, 3.03; 95% CI, 1.40–6.37; p < 0.01), shock (odds ratio, 5.73; 95% CI, 2.85–11.5; p < 0.01), and multiple organ dysfunction syndrome (odds ratio, 10.41; 95% CI, 5.89–10.40; p < 0.01). In the multivariate analysis, platelet count less than 50 × 10 9 /L (odds ratio, 138; 95% CI, 42.6–449; p < 0.01) and age less than 12 months (odds ratio, 3.06; 95% CI, 1.03–9.10; p = 0.02) remained statistically significant determinants. The attending physicians were asked why they gave a platelet transfusion; the most frequent justification was prophylactic platelet transfusion in presence of thrombocytopenia with an average pretransfusion platelet count of 32 ± 27 × 10 9 /L (median, 21), followed by active bleeding with an average pretransfusion platelet count of 76 ± 39 × 10 9 /L (median, 72). Platelet transfusions were associated with the subsequent development of multiple organ dysfunction syndrome (odds ratio, 2.53; 95% CI, 1.18–5.43; p = 0.03) and mortality (odds ratio, 10.1; 95% CI, 4.48–22.7; p < 0.01). Conclusions: Among children, 7.1% received at least one platelet transfusion while in PICU. Thrombocytopenia and active bleeding were significant determinants of platelet transfusion. Platelet transfusions were associated with the development of multiple organ dysfunction syndrome and increased mortality.